Akibat Hukum Pemotongan Upah Pekerja Penerima Bantuan Subsidi Upah (BSU) oleh Pengusaha Waroeng Spesial Sambal (WSS) Ditinjau dari Hukum Ketenagakerjaan - Salaztwina Nurjayanty; Holyness N Singadimedja; Agus Pratiwi (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this research is to determine the legal consequences for workers of the issuance of WSS Indonesia Director's Letter Number: 0307/WSS/SDM-Kesra/SK-BSU SS/X/2022 regarding BSU's stance in the form of wage cuts for WSS Indonesia Personnel in terms of labor law provisions, as well as to understand the legal protection for WSS workers receiving BSU who are subject to wage cuts based on the issuance of a WSS Director's Letter in terms of labor law provisions. This research uses normative juridical methods with analytical descriptive specifications. The research was conducted using data sources based on positive law which is secondary data, including primary legal sources and secondary legal sources. The data collection technique used is a literature study which is then analyzed qualitatively, by describing the data which is connected and arranged systematically. Based on the research results, the issuance of the WSS Director's Letter regarding wage cuts for workers receiving BSU has deprived workers of their right to wages, violated provisions regarding wage obligations for workers, and deprived workers of their right to receive government assistance. Therefore, there is an obligation for WSS to comply with administrative sanctions based on applicable laws and regulations. Legal protection for WSS workers receiving BSU who are affected by wage cuts can be seen from the existence of statutory regulations governing workers' wages as well as the existence of institutions and mechanisms for resolving rights disputes to protect workers' rights so that they can be fulfilled.